ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Agung Hidayat Qisthie, 13.05.52.0122; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2017)
The purpose of this research is to analyze the influence of liquidity, leverage, company size, sales growth, institutional ownership, managerial ownership, and independent commissioner to financial distress. Financial distress is a condition in which the company has financial difficulties. This research is done because financial distress is a serious problem for the company because it can impact on bankruptcy. The population in this study is the data of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the year 2013-2015. Sample selection using purposive sampling method and obtained 142 data of manufacturing company. Sources of data in this study using secondary data obtained from the website www.idx.co.id. The method of analysis used in this research is logistic regression analysis. The results of this study indicate that (1) liquidity has a significant influence on financial distress, (2) leverage has a significant influence on financial distress, (3) firm size has no significant effect on financial distress, (4) sales growth has influence (5) institutional ownership has no significant effect on financial distress, (7) independent commissioners have no significant effect on financial distress.Keywords: Financial Distress, Liquidity, Leverage, Company Size, Sales Growth, Institutional Ownership, Managerial Ownership, and Independent Commissioner